Differences in the neovascular potential of thymus versus subcutaneous adipose‐derived stem cells from patients with myocardial ischaemia. (3rd January 2018) - Oliva‐Olivera, Wilfredo; Coín‐Aragüez, Leticia; Lhamyani, Said; Salas, Julián; Gentile, Adriana‐Mariel; Romero‐Zerbo, Silvana‐Yanina; Zayed, Hatem; Valderrama, Jf; Tinahones, Francisco José; El Bekay, Rajaa
Abstract: Adipose tissue‐derived multipotent mesenchymal cells (ASCs) participate in the information of blood vessels under hypoxic conditions. It is probable that the susceptibility of ASCs to the influence of age and ageing‐associated pathologies compromises their therapeutic effectiveness depending on the adipose tissue depot. Our aim was to examine the neovascular potential under hypoxic conditions of ASCs‐derived from thymic (thymASCs) and subcutaneous (subASCs) adipose tissue from 39 subjects with and without type 2 diabetes mellitus (T2DM) and of different ages who were undergoing coronary bypass surgery. We confirmed a significant decrease in the percentage of CD34 + CD31 − CD45 − subASCs in the cell yield of subASCs and in the survival of cultured endothelial cells in the medium conditioned by the hypox‐subASCs with increasing patient age, which was not observed in thymASCs. Whereas the length of the tubules generated by hypox‐subASCs tended to correlate negatively with patient age, tubule formation capacity of the hypoxic thymASCs increased significantly. Compared with subASCs, thymASCs from subjects over age 65 and without T2DM showed higher cell yield, tubule formation capacity, vascular endothelial growth factor secretion levels, and ability to promote endothelial cell survival in their conditioned medium. Deterioration in subASCs neovascular potential relative to thymASCs derived from these subjects was accompanied by higher expression levels of NOX4 mRNA and fibrotic proteins. Our results indicate that thymASCs from patients over age 65 and without T2DM have a higher angiogenic potential than those from the other patient groups, suggesting they may be a good candidate for angiogenic therapy in subjects undergoing coronary bypass surgery.